The Effectiveness Of Graphic Programs In Industrial Product Design (Journal of the College of Basic Education, 2026)
The study aimed to identify the effectiveness of graphic programs in industrial product design. The study population may have been all employees in industrial companies operating in Baghdad, while the targeted research sample size was (100) male and female employees from the administrative employees working in the Light Industries Company. To achieve the study objective, the descriptive analytical approach was used by developing a questionnaire. The results of the study showed that the general arithmetic mean of the sample members' answers to the paragraphs that measure the factors affecting graphic program strategies came with a high degree of appreciation. The results also showed the existence of a significant statistically significant effect of the influencing factors (cost, quality, and competitive advantage) combined on product design strategies in industrial companies in their combined dimensions (efficiency and effectiveness, customer satisfaction, and profitability rate). The study recommended that the companies surveyed should continuously benefit from the latest technical developments in graphic software in order to develop their industrial products.